HTLV-1/2 prevalence in two Amazonian communities - Elida C.G. Mata; Roberto M. Bezerra; Aldo A. Proietti Júnior; Luana K.S. Pamplona; Lilian O. Gomes; Valmir C. Corrêa; Jordan S.R. Caluff; Geanny S. Borges; J. Casseb; L.I.B. Kanzaki (Elsevier, 2018)
Introduction: The human T-cell lymphotropic virus type 1 (HTLV-1) is aetiologically linked to myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T cell leukaemia (ATL) besides other less incident pathologies, while the type 2 has not been definitively linked to any diseases. Objectives: To determine the HTLV-1/2 seroprevalence in two Brazilian communities in northern Brazil. Methods: In 2010 and 2015, HTLV-1/2 serological surveys were carried out in the Oiapoque county at the Brazilian border with French Guiana and in Santa Cruz do Arari, Marajó Island. Serum and breast-milk samples from 317 women (pregnant, lactating and non-pregnant non-lactating) resident in the Oiapoque county, together with serum samples from 217 females and 70 males living in Santa Cruz do Arari county, were twice screened by two distinct commercial immunoassay methods for antibodies to HTLV-1/2. Seroreactivity was confirmed by a commercial Western blot technique. Participants were interviewed for data concerning their health, socioeconomic and educational status. Results: None of the Oiapoque women, mostly young and descendants of migrants, had antibodies to HTLV-1/2, despite the high HTLV-1 prevalence in neighbouring French Guiana and Caribbean Islands, while five females and three males living in Santa Cruz do Arari county were HTLV-1 infected as confirmed by Western blot testing. In contrast, the Santa Cruz do Arari community lives in relative isolation and is descended mostly from black African people with high consanguinity. Conclusion: Despite the proximity between Oiapoque and Santa Cruz do Arari counties, ethnic, age differences, community isolation and consanguinity may explain the distinct HTLV-1/2 epidemiology in these areas of northern Brazil.